2011
DOI: 10.1364/boe.2.000385
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-photo-acoustic imaging

Abstract: Magneto-photo-acoustic imaging, a technique based on the synergy of magneto-motive ultrasound, photoacoustic and ultrasound imaging, is introduced. Hybrid nanoconstructs, liposomes encapsulating gold nanorods and iron oxide nanoparticles, were used as a dual-contrast agent for magneto-photo-acoustic imaging. Tissue-mimicking phantom and macrophage cells embedded in ex vivo porcine tissue were used to demonstrate that magneto-photo-acoustic imaging is capable of visualizing the location of cells or tissues labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 21 publications
1
65
0
Order By: Relevance
“…These particles can be used to couple PA imaging with magnetic resonance imaging (MRI) or magnetomotive ultrasound (MMUS) imaging. Nanostars, 117 nanoroses, 61 pearl necklaces, 111 nanowantons, 6 iron oxide and gold-coupled core-shell nanoparticles, 36 and liposomes containing iron oxide nanospheres and gold nanorods 84 have all been developed. Other nanoparticles have recently been synthesized which produce contrast in US and PA imagings.…”
Section: Multi-modal Contrast Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These particles can be used to couple PA imaging with magnetic resonance imaging (MRI) or magnetomotive ultrasound (MMUS) imaging. Nanostars, 117 nanoroses, 61 pearl necklaces, 111 nanowantons, 6 iron oxide and gold-coupled core-shell nanoparticles, 36 and liposomes containing iron oxide nanospheres and gold nanorods 84 have all been developed. Other nanoparticles have recently been synthesized which produce contrast in US and PA imagings.…”
Section: Multi-modal Contrast Agentsmentioning
confidence: 99%
“…4e, 4f). 36,84 Similar techniques have been proposed to trap circulating tumor cells in the blood stream or lymphatic system. 17,35 CONCLUSIONS PA imaging shows great promise for use in a wide array of clinical procedures, ranging from diagnosis to therapy guidance.…”
Section: Multi-modal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, magneto-plasmonic nanoparticles were used to increase contrast in dark-field imaging of labeled cells by applying a temporal signal modulation via an external electromagnet [3][4][5] . More recently, a similar principle was applied in development of a new imaging modality -magneto-photoacoustic imaging, where magneto-plasmonic nanoparticles enable great improvements in contrast and signal-to-background ratio 6,7 . It was also shown that the hybrid nanoparticles can be used for simultaneous capture and detection of circulating tumor cells in whole blood and in vivo 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar ideas using hybrid contrast agents with magnetic properties have also been proposed for US and PA imaging. 22,23 In previous results from our laboratory, micro-scale magnetic particles (MMPs) were used to mimic magnetic contrast agent targeted cells in a blood vessel. [19][20][21] In the current study, nanometer-scale composite contrast agents consisting of a highly optical absorptive gold nanorod (GNR) coupled with magnetic nanospheres (MNSs) were chemically linked (i.e., targeted) to micro-scale beads mimicking CTCs.…”
Section: Introductionmentioning
confidence: 99%